Uso de imagens obtidas por aeronave remotamente pilotada (ARP) para mensuração do volume de toras de madeira empilhadas em pátio industrial - Heraki, Leonardo (2020)
The volumetric estimation of stacked logs can be made using RPA with cameras that capture high quality images to build 3D Models on photogrammetry software. This study aimed to quantify the volume of stacked logs in a storage yard through high spatial resolution aerial images obtained by remotely piloted aircraft (RPA). The volumetric estimation were tested using Structure from Motion-Multi View Stereo (SfM-MVS) in relation the convencional method of measurement. The scientific study was carried out in the storage yard of the company Agrosepac Serrados Ltda, located in the city of Mallet. The yard area is 0.55 hectares, where It was allocated ten ground points (GPC’s) georeferenced by GEOMAX RTK Zennith 25 receiver, with GPS constellation L1 / L2 / L2C and GLONASS L1 / L2. The aerial images of the storage yard were captured by a remotely piloted aircraft (RPA) DJI PHANTOM 4 Advanced with camera FC6310. It was tested three different flight altitude (60, 80 and 100m). The survey of aerial images with remotely piloted aircraft (RPA) combined with photogrammetry softwares to build digital surface models (DSM), makes it possible to carry out volumetric measurements of stacked logs. The volumetric measurements using the SfM-MVS, from images obtained on 60, 80 and 100m flight altitude, but there is no significant difference in relation to conventional method of measurement. The treatment 4 (control), that is the conventional method, the averages of the volumetric estimates tested in treatments 1, 2 and 3, using the SfM-MVS technique, using images obtained at 60, 80 and 100m flight altitude, their showed variations of 17, 50%, 14.93% and 8.31%, respectively. It showed results within 10% tolerance by the forest industry, therefore the best models for obtaining volumetric estimates were considered, when it used aerial images by RPA flying 100m altitude.